The international ship-registers in Europe - Faggioni, Camilla (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
The article underlines the issues surrounding international (second) ship-registers from a labour law perspective. The registers specifically analysed are the French, German, and Italian registers. The spread of international registers in the EU is bringing the work- ing conditions onboard European ships into line with those prevalent in developing countries. Moreover, these registers can lead to wage dumping and pay discrimination, creating challenges for the employment prospects of European seafarers. Consequently, on a few occasions their legitimacy in relation to constitutional principles and European law has been questioned. Given their impact on workers, the author believes interna- tional registers cannot be considered a viable solution to the shipping crisis affecting the European Union Member States.
Keywords: delovno pravo; globalizacija; ladje; mednarodno pomorsko pravo; pomorski promet; pomorsko pravo; registri